2018 IEEE 18th International Conference on Advanced Learning Technologies (ICALT) 2018
DOI: 10.1109/icalt.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Learning Engagement in Challenge-Based Online Learning

Abstract: Vast amounts of educational data created by learners interacting with digital learning tools open up the opportunity to gain insights for improving education at a new level of evidence-based research into learning and teaching. This study is part of a research programme investigating the dynamics and impacts of learning engagement in a challengebased online learning environment. Learning engagement is a multidimensional concept which includes an individual's ability to behaviourally, cognitively, emotionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Online learning has emerged as a critical alternative to higher education access, especially with limitations to face-to-face learning imposed by pandemics such as COVID-19. In developing countries, frequently beset by resource and infrastructural constraints, access to online learning can be challenging (Ifenthaler et al, 2018). This study was conducted to evaluate the online learning experience at a Kenyan School of Pharmacy during the academic year 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Online learning has emerged as a critical alternative to higher education access, especially with limitations to face-to-face learning imposed by pandemics such as COVID-19. In developing countries, frequently beset by resource and infrastructural constraints, access to online learning can be challenging (Ifenthaler et al, 2018). This study was conducted to evaluate the online learning experience at a Kenyan School of Pharmacy during the academic year 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Genera un mayor compromiso en los estudiantes (Ifenthaler et al, 2018). Enfatiza la dificultad del reto con el propósito de desarrollar la innovación en los estudiantes (Lin & Chen, 2017).…”
Section: Experiencialunclassified
“…Challenge-based learning enables students to freely select what and when to study and to interact with digital learning materials. Ifenthaler [9] found that learning participation in challengebased online learning environments was positively related to learning effectiveness.…”
Section: Challenge-based Learningmentioning
confidence: 99%